The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1371/journal.pone.0138605
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Dysfunction Induced by Obesity Is Not Related to β-Adrenergic System Impairment at the Receptor-Signalling Pathway

Abstract: Obesity has been shown to impair myocardial performance. Some factors have been suggested as responsible for possible cardiac abnormalities in models of obesity, among them beta-adrenergic (βA) system, an important mechanism of regulation of myocardial contraction and relaxation. The objective of present study was to evaluate the involvement of βA system components in myocardial dysfunction induced by obesity. Thirty-day-old male Wistar rats were distributed in control (C, n = 25) and obese (Ob, n = 25) groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 80 publications
(118 reference statements)
7
47
1
4
Order By: Relevance
“…; Ferron et al. ), and oppose to Carroll et al. (), who observed decreased responsiveness to isoproterenol in obese rabbits fed with UHFD for 12 weeks.…”
Section: Discussionmentioning
confidence: 85%
“…; Ferron et al. ), and oppose to Carroll et al. (), who observed decreased responsiveness to isoproterenol in obese rabbits fed with UHFD for 12 weeks.…”
Section: Discussionmentioning
confidence: 85%
“…We have found the Wistar rat to be obesity-prone, and multiple authors have published the Wistar rat to be a susceptible rodent strain to cardiac dysfunction of a HFD [1922]. Samniang et al found 12 weeks of a HFD fed to male Wistar rats induced significantly increased body weight, plasma insulin, HOMA index, total cholesterol, and LDL levels as well as significant reductions in FS% and systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A HFD also induced cardiac autonomic imbalance, cardiac myocardial dysfunction, and increased circulating and cardiac tissue oxidative stress [21]. Many of these metabolic derangements are shared with patients who are morbidly obese with cardiac metabolic disease including hypertriglyceridemia, hypertension, glucose intolerance, and hyperleptinemia [22]. However, the relationship between obesity and heart failure development in humans is complex involving multiple different pathways that ultimately affect cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of reduced β‐adrenergic responsiveness in hearts of obese rats confirms previous findings, not only in isolated rat and rabbit hearts (Carroll et al., ; Carroll, Kyser, & Martin, ; Jiang et al., ; Lima‐Leopoldo et al., ), but also using cardiac membranes (Bass & Ritter, ; Chatelain et al., ; Strassheim et al., ), and more importantly, in vivo assessment in conscious conditions (Bunag et al., ; Bussey et al., ). In some studies, it was not possible to associate the reduced β‐adrenergic responsiveness of the obese heart with a downregulation of the β‐ARs (Carroll et al., ; Ernsberger, Koletsky, Baskin, & Foley, ; Ferron et al., ; Hohl et al., ; Minhas et al., ; Vileigas et al., ), potentially owing to differences in obese animal models and technical approaches. However, in several other studies, using obese Zucker rats, downregulation of β‐ARs was observed (Chatelain et al., ; Jiang et al., ; Strassheim et al., ), as found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, does not exclude the possibility that other β‐AR subtypes could be affected during obesity (Chatelain et al., ; Jiang et al., ; Strassheim et al., ) or play an important supportive role in the pathophysiology of obesity and diabetes (Cook et al., ; Li et al., ; Perez‐Schindler et al., ). More importantly, given that from a clinical viewpoint targeting β‐ARs with β‐blockers is commonly advised against in obese individuals owing to their unfavourable metabolic effects (Gress et al., ; Sharma et al., ) and given that β‐AR downregulation is most probably not the sole mechanism underlying the reduced β‐adrenergic responsiveness of the heart in obesity (Ferron et al., ; Vileigas et al., ), alternative mechanisms should be explored.…”
Section: Discussionmentioning
confidence: 99%